VISUALISASI HADIS DAN TRANSFORMASI OTORITAS KEAGAMAAN MELALUI ANALISIS MEME HADIS PADA AKUN INSTAGRAM @HADITS_SHAHIHH - Zulkifli Wagola (Amsal Al-Qur’an: Jurnal Al-Qur’an dan Hadis, 2026)
The spread of hadith via social media has shifted its transmission from traditional scholarly circles to visual formats. This study examines @hadits_shahihh, an Instagram account with over 120,000 followers that consistently posts hadith memes and displays Salafi affiliation. Using a qualitative descriptive-analytical method, four thematically dominant memes from 2021–2025 were analyzed through visual elements, texts, captions, and comments. Results show that meme-based hadith removes historical context, leading to fragmented understanding. Audience responses reveal three patterns: literal acceptance, meaning negotiation, and affective expressions reinforcing religious identity. The account advances Salafi ideology through selective authorities and dichotomous framing. The findings confirm that hadith memes are not merely preaching tools but arenas of interpretive contestation that shift religious authority from traditional scholarly structures to digital actors relying on popularity and visual aesthetics.